Combination of melatonin and Wnt‐4 promotes neural cell differentiation in bovine amniotic epithelial cells and recovery from spinal cord injury. Issue 3 (15th February 2016) - Gao, Yuhua; Bai, Chunyu; Zheng, Dong; Li, Changli; Zhang, Wenxiu; Li, Mei; Guan, Weijun; Ma, Yuehui
Abstract: Although melatonin has been shown to exhibit a wide variety of biological functions, its effects on promoting differentiation of neural cells remain unknown. Wnt signaling mediates major developmental processes during embryogenesis and regulates maintenance, self‐renewal, and differentiation of adult mammalian stem cells. However, the role of the noncanonical Wnt pathway during neurogenesis remains poorly understood. In this study, the amniotic epithelial cells ( AECs) were isolated from bovine amnion and incubated with various melatonin concentrations (0.01, 0.1, 1, 10, or 100 μ m ) and 5 × 10 −5 m all‐trans retinoic acid (RA) for screening optimum culture medium of neural differentiation, compared with each groups, 1 μ m melatonin and 5 × 10 −5 m RA were selected to induce neural differentiation of AECs, and then siMT1, siMT2, oWnt‐4, and siWnt‐4 were expressed in AECs to research role of these genes in neural differentiation. Efficiency of neural differentiation was evaluated after expressed above genes using flow cytometry. Cell function of neural cells was demonstrated in vivo using spinal cord injury model after cell transplantation, and damage repair of spinal cord was assessed using cell tracking and Basso, Beattie, Bresnahan Locomotor Rating Scale scores. Results demonstrated that melatonin stimulated melatonin receptor 1, which subsequently increased bovine amniotic epithelial cell vitality and promoted differentiation into neural cells. This took place through cooperation with Wnt‐4. Additionally, following cotreatment with melatonin and Wnt‐4, neurogenesis gene expression was significantly altered. Furthermore, single inhibition of melatonin receptor 1 or Wnt‐4 expression decreased expression of neurogenesis‐related genes, and bovine amniotic epithelial cell‐derived neural cells were successfully colonized into injured spinal cord, which suggested participation in tissue repair.